AKTVITAS ANTIBAKTERI EKSTRAK ETANOL BUAH MENTIMUN (Cucumis sativus Linn) TERHADAP Salmonella typhi dan Bacillus cereus SECARA IN VITRO - A.S.H. Permana; M warman (FMIPA : Universitas PGRI Adi Buana, 2016)
The objective of this studi was evaluate the antibacterial activity of Cucumber fruit against Salmonella typhidan Bacillus cereus in vitro. Ethanol extract of Cucumber fruit devided into 4 doses 100%, 75%, 50%, and25% S. typhi dan B. cereus. Amoxicillin were used as positive control and aquadest as negative control. Theresult this study showed antibacteria activity of ethanol extract Cucumber fruit inhibited the growth ofSalmonella typhi and Bacillus cereus. Antibacterial activity of Cucumber fruit 100% concentration of theextract produce inhibited zone greatest is 7,7±0,92 mm included categorized intermediate. Whereas B.cereus inhibited zone greatest is 2,6±0,39 mm, and dan included categorized weak. Keywords:Antibacterial activity, Salmonella typhi, Bacillus cereus, in vitro, Ethanol extract cucumber fruit